Antioxidative, cytoprotective and whitening activities of fragrant pear fruits at different growth stages - Jiang, Hui; Wu, Fei; Jiang, Xi; Pu, Yun-Feng; Shen, Li-Rong; Wu, Cui-Yun; Bai, Hong-Jin (Frontiers in Nutrition, 2022)
Pear is one of the most popular fruits in the world. With the fruit ripening, a series of physiological changes have taken place in fragrant pear, but up to now, the research on the metabolism and biological activity of phenolic compounds in different growth stages of fragrant pear is still lacking. In this study, four kinds of Xinjiang pears were selected as research objects, and the changes of phenolic content, antioxidant capacity, cell protection and whitening activity during fruit development were analyzed. The results showed that the phenolic content and antioxidant capacity of four pear varieties presented a decreasing trend throughout the developmental stages. The phenolic content and antioxidant activity of the four pears in the young fruit stage were the highest, and the active ingredients of the Nanguo pear were higher than the other three pear fruits. Pear extract could protect cells by eliminating excessive ROS in cells, especially in young fruit stage. The western blot results showed that the extract of fragrant pear in the young fruit stage could inhibit the expression of TYR, TYR1 and MITF in B16 cells, and it was speculated that the extract of fragrant pear in the young fruit stage might have good whitening activity. Therefore, the findings suggest that young pear display a good antioxidant potential and could have a good application prospect in food preservation and health product industry.